Pengaruh Stres Kerja, Beban Kerja, dan Motivasi Terhadap Kinerja Pegawai pada Perusahaan Daerah Air Minum (PDAM) Tirtauli Pematangsiantar - Nasrani Margareth Sitorus; Elperida Sinurat; Tiur Rajagukguk (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
The success of an organization depends on its ability to manage the various resources it has. This study aims to determine the effect of work stress, workload and motivation on employee performance at the Regional Drinking Water Company (PDAM) Tirtauli Pematangsiantar. This study uses quantitative research. The sample in this study was 71 respondents. Based on the results of the t hypothesis test, the work stress t-test value was obtained 0.213 <t table 1.996, and a significance value of 0.832> 0.05, so partially work stress has a positive and insignificant effect on employee performance, the workload t-test value is 1.641 <t table 1.996, and a significance value of 0.106> 0.05, so partially workload has a positive and insignificant effect on employee performance, the motivation t-test value is 8.621> t table 1.996, and a significance value of 0.000 <0.05, so partially motivation has a positive and significant effect on employee performance. Based on the results of the F hypothesis test, the Fcount value is 56.274> 2.74 and the significance value of F is 0.000 <0.05, so simultaneously work stress, workload and motivation have a significant effect on employee performance. Based on the results of the determination coefficient analysis, the Adjusted R-Square value is 0.703 or 70.3%, meaning that the effect of work stress, workload and motivation on employee performance is 70.3%